Компрессирование описания визуальных объектов путем фильтрации его компонент по критерию стабильности - Власенко, Н. В.; Канунников, А. С.; Машталир, С. В. (НТУ "ХПИ", 2013)
Ways of compression space structural features images using the criterion of stability of their values on the training set of geometric transformations explores in article. A concise description is based on the computed subset of stable points. Experimental results on image classification based on the proposed methods confirm their high efficiency.
Keywords: классификация изображений; описание структурное; сжатие; инвариантность; затраты вычислительные